The Role of “Digital Warrior Teachers” in Optimizing the Utilization of Interactive Flat Panel through the Technology Ambassador Community - Anijar Hapni Siregar; Maya Novita Sari (Journal of Educational Sciences, 2026)
This study aims to analyze the strategic role of "Digital Warrior Teachers” (DWT) within the Technology Ambassador community in optimizing the use of Interactive Flat Panels (IFP) in classroom learning, as well as to develop a community-based educational human resource management concept. This study uses a qualitative case study approach. Data were collected through Focus Group Discussions (FGDs) with 10 DWTs from various regions in Indonesia, netnographic observations in the Technology Ambassador WhatsApp community, and document analysis of teaching modules and IFP usage logs. The results identified three collective mechanisms: (1) socio-emotional: reducing teachers' technological anxiety through peer mentoring and real-life demonstrations; (2) interactive-pedagogical: transforming IFP into a student-centered interactive learning center; (3) managerial-collaborative: building a digital asset repository and policy bridges. The success of IFP optimization does not rely on individual technical abilities but on the collective mechanisms implemented by DWTs through the Technology Ambassador community. This study concludes that strengthening professional communities is more decisive for digital transformation success than conventional technical training. Further research is recommended to explore the internal dynamics of trust and social solidarity within the community through long-term netnographic or phenomenological studies.